2008
DOI: 10.1371/journal.pone.0002473
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy in Dcx Knockout Mice Associated with Discrete Lamination Defects and Enhanced Excitability in the Hippocampus

Abstract: Patients with Doublecortin (DCX) mutations have severe cortical malformations associated with mental retardation and epilepsy. Dcx knockout (KO) mice show no major isocortical abnormalities, but have discrete hippocampal defects. We questioned the functional consequences of these defects and report here that Dcx KO mice are hyperactive and exhibit spontaneous convulsive seizures. Changes in neuropeptide Y and calbindin expression, consistent with seizure occurrence, were detected in a large proportion of KO an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 56 publications
5
66
1
Order By: Relevance
“…Pyramidal cells displayed morphological abnormalities, as they were smaller with a reduced total dendritic length, and were more excitable than WT cells. In vitro hyperexcitability and spontaneous epilepsy are characteristic of this mouse model [107].…”
Section: 212bmentioning
confidence: 88%
“…Pyramidal cells displayed morphological abnormalities, as they were smaller with a reduced total dendritic length, and were more excitable than WT cells. In vitro hyperexcitability and spontaneous epilepsy are characteristic of this mouse model [107].…”
Section: 212bmentioning
confidence: 88%
“…The convergence of these features in a mouse model could have significant consequences for circuit information processing and/or contribute to the generation of pathological network excitability associated with type I lissencephaly. A number of genetically based animal models of MCD have been developed, and most show robust hyperexcitability and/or spontaneous seizures (Wenzel et al, 2001;Kellinghaus et al 2004;Patel et al, 2004;Kwon et al, 2006;Harrington et al, 2007;Patrylo and Willingham, 2007;Nosten-Bertrand et al, 2008;Greenwood et al, 2009;Kerjan et al, 2009). When synaptic mechanisms have been investigated, these studies have typically reported postsynaptic alterations in glutamatergic excitatory Auerbach et al, 2011;Bateup et al, 2011;Luikart et al, 2011) or GABAergic inhibitory currents (Trotter et al, 2006;Ackman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Nosten-Bertrand et al (24) recently published that Dcx single nulls can develop rare seizures. A potential explanation for this discrepancy is the use of the C57BL/6N (B6) background by Nosten-Bertrand et al (24), which is associated with a lowered seizure threshold in some mutant mice (25), whereas we used a mixed 129/SvJ and B6 background.…”
Section: Discussionmentioning
confidence: 99%